Outcomes in HeartMate II Patients With No Antiplatelet Therapy: 2-Year Results From the European TRACE Study - Netuka, Ivan; Litzler, Pierre-Yves; Berchtold-Herz, Michael; Flecher, Erwan; Zimpfer, Daniel; Damme, Laura; Sundareswaran, Kartik S; Farrar, David J; Schmitto, Jan D; EU TRACE Investigators (The Annals of thoracic surgery, 2017)
BACKGROUND: Current recommendations of antithrombotic therapy for HeartMate II (HMII) patients include the use of both an anticoagulant and an antiplatelet agent. Because bleeding is still the most frequent adverse event, the TRACE (STudy of Reduced Anti-Coagulation/Anti-platelet Therapy in Patients with the HeartMatE II) study was initiated to evaluate the incidence of adverse events in HMII patients on reduced antithrombotic (RT) therapy. METHODS: HMII patients (n = 101) from nine centers were enrolled in the European arm of TRACE and were managed on a single anticoagulant (vitamin K antagonist) with no antiplatelet agents. An analysis of bleeding and thrombotic adverse events from all 101 patients with 2-year follow-up after initiation of RT therapy is reported here. RESULTS: Median age was 56 years (range, 18 to 72 years), 93% were men, 70% had an Interagency Registry for Mechanically Assisted Circulatory Support profile 1 to 3, and 82% received the HMII as a bridge to transplantation. Ninety-two percent were placed on RT therapy as a center standard of care or due to physician preference and 6% as a response to bleeding. Median HMII support duration on RT therapy was 25 months (range, 1 to 93 months). Median international normalized ratio was 2.31 [quartile 1 to quartile 3: 2.07 to 2.60]. At 2 years, freedom from bleeding, ischemic stroke, hemorrhagic stroke, and pump thrombosis after initiation of RT therapy was 81% ± 6%, 96% ± 2%, 94% ± 3%, and 94% ± 3%, respectively. CONCLUSIONS: The 2-year analysis of the observational European TRACE study suggests that managing HMII patients with a vitamin K antagonist with a target international normalized ratio of 2.3 without antiplatelet therapy may help to reduce the incidence of major bleeding without increasing the risk of thromboembolic events, including ischemic stroke and pump thrombosis.
Keywords: senioři; Male; Europe; Incidence; Time Factors; mladiství; Cohort Studies; výsledek terapie; Evropa; Middle Aged; mužské pohlaví; incidence; Adult; mladý dospělý; kohortové studie; inhibitory agregace trombocytů; Young Adult; antikoagulancia; ženské pohlaví; Platelet Aggregation Inhibitors; Humans; Postoperative Hemorrhage; Anticoagulants; pooperační krvácení; časové faktory; lidé středního věku; srdeční selhání; Heart-Assist Devices; dospělí; Female; Aged; Adolescent; Treatment Outcome; Heart Failure; lidé; podpůrné srdeční systémy